2010
DOI: 10.1038/onc.2010.91
|View full text |Cite
|
Sign up to set email alerts
|

PKG inhibits TCF signaling in colon cancer cells by blocking β-catenin expression and activating FOXO4

Abstract: Activation of cGMP-dependent protein kinase (PKG) has antitumor effects in colon cancer cells but the mechanisms are not fully understood. The present study has examined the regulation of β-catenin/TCF signaling, since this pathway has been highlighted as central to the antitumor effects of PKG. We show that PKG activation in SW620 cells results in reduced β-catenin expression and a dramatic inhibition of TCF-dependent transcription. PKG did not affect protein stability, nor did it increase phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 56 publications
3
54
0
Order By: Relevance
“…The MUC2-luciferase reporter assay was described previously. 18,34 c-Jun-and ATF2-luciferase reporter assays were performed using PathDetect c-JUN transReporting System (Agilent Technologies, Santa Clara, CA, USA) according to the manufacturer's protocols. Dominant-negative JNK was a generous gift from Dr. Shuang Huang (Georgia Regents University, Augusta, GA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The MUC2-luciferase reporter assay was described previously. 18,34 c-Jun-and ATF2-luciferase reporter assays were performed using PathDetect c-JUN transReporting System (Agilent Technologies, Santa Clara, CA, USA) according to the manufacturer's protocols. Dominant-negative JNK was a generous gift from Dr. Shuang Huang (Georgia Regents University, Augusta, GA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Gene-specific primers were designed using the National Center for Biotechnology Information Primer Blast Software as follows: human PKG2 (forward: 5=-AGCCCGCTTCAGGCCTCT CC-3=, reverse: 5=-AGTCGACCCTCT-GCCAGCAC-3=), human Sox9 (forward: 5=-GATCTGAAGAAGGA GAGCGAGGAGGACAAG-3=, reverse: 5=-CGTTGGGGGAGATGT-GCGTCTGCTC-3=), human MUC2 (forward: 5=-CCGCTGGAGCCG-TATCTGCG-3=, reverse: 5=-CGGGGCAGGGCAGGTCTTTG-3=), human CDX2 (forward: 5=-AGGCAGAAGAGCCGCGAGGA-3=, reverse: 5=-CCAGTCCTCCCGGAGTGGG G-3=), mouse PKG2 (forward: 5=-GTGGCGGAGGACGCCAAGAC-3=, reverse: 5=-AGGCCTG-CAGTGG GCTTCCT-3=), and common hypoxanthine phosphoribosyltransferase 1 (HPRT1) (forward: 5=-GCGTCGTGATTAGCGATGAT-GAAC-3=, reverse: 5=-CCTCCCATCTCCTTCATGACATCT-3=). Luciferase reporter assays were performed as described previously (19). The Flag-Sox9, MUC2-, and CDX2-luciferase reporter constructs were described previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have identified several pathways that potentially mediate the antiproliferative effects of cGMP, including calcium entry through cyclic nucleotide gated channels (16,35), inhibition of ERK (37), ␤-catenin/TCF (19), and more recently, AKT (24). However, there are significant gaps in knowledge of the immediate signaling events, and comparatively very little known about cGMP signaling mechanisms in vivo.…”
mentioning
confidence: 99%
“…35 Briefly, cells were cultured in 12-well plates, and at 80% confluence the assays were performed by transfecting triplicate wells with luciferase reporter plasmids using Lipofectamine …”
Section: Foxo Reporter Assaymentioning
confidence: 99%